Handbook of Phenomenological Aesthetics - Sepp, Hans Rainer; Embree, Lester (Dordrecht Springer, 2010)
The first and only comprehensive and thoroughly-refereed work on phenomenological aestheticsExplains the clear relation between phenomenology and aesthetics, two major sub-disciplines of philosophyCombines philosophical reflections on beauty, art and sensation with views on aesthetics from great thinkers such as Sartre, Heidegger and DerridaThe potentiality of phenomenological aesthetics is enormous, many figures have contributed to it during a time span of over a century, but this is the first work thoroughly to show its breadth, depth, and continuing fecundity. Moritz Geiger, Roman Ingarden, Fritz Kaufmann, Jean-Paul Sartre, Maurice Merleau-Ponty, and Mikel Dufrenne are the central figures and receive substantial treatment. A score of other influential individuals, including Antonio Banfi, Simone de Beauvoir, Oskar Becker, Jacques Derrida, Hans-Georg Gadamer, Martin Heidegger, Michel Henry, Dietrich von Hildebrand, Maurice Natanson, Nishida Kitaro, Jose Ortega y Gasset, Jan Patocka, Paul Ricoeur, Heinrich Rombach, Max Scheler, Alfred Schutz, Gustav Spet, and France Veber also have entries devoted to them. In addition, there are over two dozen entries on such topics such as dream, empathy, enjoyment, imagination, sensation, on style, ecology, gender, and interculturality, and then on areas including architecture, film, and theater. The introduction includes an extensive sketch of the history of phenomenological investigation in this sub-discipline of philosophy. All entries are written by the best relevant specialists, all the entries have bibliographies, and a selected bibliography for the whole is appended. This handbook will be the foundation for many more decades of investigation.
Keywords: Esthetics; Philosophy